Optimal control of spins by Analytical Lie Algebraic Derivatives. (July 2021) - Foroozandeh, Mohammadali; Singh, Pranav
Abstract: Computation of derivatives (gradient and Hessian) of a fidelity function is one of the most crucial steps in many optimization algorithms. Having access to accurate methods for computing these derivatives is even more desirable where the optimization process requires propagation of these computations over many steps, which is particularly important in optimal control of spin systems. Here we propose a novel numerical approach, ESCALADE (Efficient Spin Control using Analytical Lie Algebraic Derivatives), that offers the exact first and second derivatives of the fidelity function by taking advantage of the properties of the Lie group of 2 × 2 unitary matrices, SU ( 2 ), and its Lie algebra, the Lie algebra of skew-Hermitian matrices, su ( 2 ) . A full mathematical treatment of the proposed method along with some numerical examples are presented.